In-situ observations of swarming pelagic tunicate Pegea confoederata (Forskål, 1775) (Tunicata: Thaliacea) in coral reef habitats of Kuwait - Amani Al-Yaqout; Manickam Nithyanandan; Yiannis Issaris; Rakhesh Madhusoodhanan; Gopkirishna Mantha; Mohammad Al-Kandari; Musaad Al-Roumi; Stamatis Zogaris (Kuwait Journal of Science)
Pelagic tunicates (order Salpida) have the highest filtration rates among filter feeding marine zooplankton. This is the first-ever in situ observation of the salp, Pegea confoederata (Forskål, 1775), in northwestern Arabian Gulf (NWAG), off Kuwait. Swarms of P. confoederata with chain-like blastozooids (∼1 ​m) and solitary oozoids were observed in offshore coral reef habitats. Coastal fishes, Diplodus sargus kotschyi and Abudefdef vaigaiensis, were observed feeding on P. confoederata tests. In Kuwait, higher summer density of phytoplankton (<20 ​μm) supports P. confoederata aggregation. Concerted studies on salps in the Arabian Gulf may offer insights into pelagic carbon cycling pathways and carbon sequestration.